2018
DOI: 10.2147/idr.s173804
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-resistant <em>Pseudomonas aeruginosa</em> from sputum of patients with cystic fibrosis demonstrates a high rate of susceptibility to ceftazidime&ndash;avibactam

Abstract: PurposeCeftazidime–avibactam is a novel antimicrobial combining a third-generation cephalosporin with a non-β-lactam β-lactamase inhibitor that was recently approved to treat Gram-negative hospital- and ventilator-acquired pneumonia. The use of ceftazidime–avibactam to treat Pseudomonas aeruginosa respiratory infections in patients with cystic fibrosis (CF) has not been evaluated. In this study, we assessed the ceftazidime–avibactam susceptibility of multidrug-resistant (MDR) P. aeruginosa sputum isolates from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…It was observed that almost all strains carried the ampC gene (97.9%), related to cephalosporins resistance. This alarming incidence of ampC (or its overexpression) in clinical isolates of P. aeruginosa was also reported by other authors [45,46]. Studies have shown that the rates of molecular detection of ampC has varied among clinical isolates of P. aeruginosa.…”
Section: Discussionsupporting
confidence: 75%
“…It was observed that almost all strains carried the ampC gene (97.9%), related to cephalosporins resistance. This alarming incidence of ampC (or its overexpression) in clinical isolates of P. aeruginosa was also reported by other authors [45,46]. Studies have shown that the rates of molecular detection of ampC has varied among clinical isolates of P. aeruginosa.…”
Section: Discussionsupporting
confidence: 75%
“…An additional use could be the treatment of lung infections caused by P. aeruginosa in patients with cystic fibrosis, for which fluoroquinolones are the only available oral antibiotics. 76,77 Since >65% P. aeruginosa isolates express the AmpC β-lactamase, 78 it is possible that our prodrug approach could be used treat the infection without the associated damage to the microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that C/T had higher in vitro efficacy against bloodstream and urinary tract infections than other beta-lactam antibiotics and carbapenems [14,[28][29][30][31][32][33] . In vitro susceptibility to CZA in lower respiratory tract infections caused by resistant P. aeruginosa was also reported to be high [34] .…”
Section: 1%mentioning
confidence: 99%